2021
DOI: 10.1186/s12912-021-00553-y
|View full text |Cite
|
Sign up to set email alerts
|

NICU and postpartum nurse perspectives on involving fathers in newborn care: a qualitative study

Abstract: Background Perinatal care nurses are well positioned to provide the education and support new fathers need to navigate the transition to fatherhood and to encourage positive father involvement from the earliest hours of a child’s life. To effectively serve fathers in perinatal settings, it is important to understand the attitudes, beliefs, and behaviors of healthcare providers that may encourage and engage them, or alternatively alienate and discourage them. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Additionally, research may identify a need to provide nurses with training and education to improve attitudes and practices toward FCC. Studies conducted in postpartum and other healthcare contexts have found that nurses often hold attitudes inconsistent with and experience challenges implementing family-centered models of care [ 27 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research may identify a need to provide nurses with training and education to improve attitudes and practices toward FCC. Studies conducted in postpartum and other healthcare contexts have found that nurses often hold attitudes inconsistent with and experience challenges implementing family-centered models of care [ 27 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to social norms of masculinity in Western societies, where men tend not to communicate their needs to others ( 60 , 66 ). Other explanations may be the primary focus of postpartum care (mother and child) and the views HCPs have of fathers, leading to inequalities in care provision ( 59 , 67 ). Different parental expectations may explain this difference ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the routine difficulties and responsibilities of having a baby, delivering a preterm baby can be a particularly challenging experience for the parents. The duration of the baby's hospital stay, the seriousness of the health problems, parents' sources of support, can affect parental coping 9,11,12 . Nurses should play an active role in the adaptation of the parents to infant care after the birth of the preterm baby, both in the hospital and during home care after discharge 9,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the baby's hospital stay, the seriousness of the health problems, parents' sources of support, can affect parental coping 9,11,12 . Nurses should play an active role in the adaptation of the parents to infant care after the birth of the preterm baby, both in the hospital and during home care after discharge 9,11,12 . A detailed understanding of the experiences of the parents will facilitate the adaptation and acceptance of the parents and contribute to the development of the parent role.…”
Section: Introductionmentioning
confidence: 99%